Role of Biofilm in Reinfection in Catheter-associated Urinary Tract Infection in Iraqi Women - Likaa Mahdi (Journal of Global Pharma Technology, 2019)
Women hinge on knowledge of antimicrobial susceptibility patterns in the Iraq country of the practitioner. We conducted a survey of antimicrobial susceptibilities of 72 urine samples from catheterized women patient.  Isolates recovered from urine samples April 2014 to July 2014, samples collected from urinary catheterized women patient in Al-Yarmouk hospital in Baghdad/ Iraq. Resistance uropathogen (E. coli, Acinetobacter baumannii, Enterobacter Spp, Enterococcus faecalis, Klebsiella Pneumoniae, Proteus mirabilis) isolates to Amoxicillin and Gentamicin combined with high biofilm formation.  Escherichia coli are the majority common micro objects concerned in community-acquired -UTI in women. UTI which was cause by uropatho-genic; Isolates can eventually re-infection Acinetobacter baumannii (n=6), E. coli (n = 9), Enterococcus faecalis (n=3), Klebsiella Pneumoniae (n=2), Enterobacter Spp. (n=2) and Proteus mirabilis (n=5). The production of E. coli biofilms in-vitro was considerably common with strains the causes the biofilms. Biofilm assay could be supportive to select required patients for healing advance to eliminate unrelenting biofilm-formation.